Technological solutions for the efficient protection of workers in the track area - Jędrzej Burek (Przegląd Komunikacyjny)
Abstract: Work on and in the vicinity of active railway tracks or other tracks is particularly hazardous work. They involve high risks for workers who may be hit or run over by moving rail vehicles or track machinery. Workers may also be electrocuted by the overhead catenary or overhead electrical network, which for non-traction purposes is supplied with 3000 volts DC. To ensure an adequate level of safety during this type of work, active tracks should be cordoned off and marked in accordance with railway regulations. Guidelines for securing the site of works carried out on closed track during the operation of railway vehicles on live track at a speed of V ≥ 100 km/h are defined in Railway Instruction Id-18. All types of construction work on live railway lines and overhead contact lines may only be carried out on the basis of the Instruction for Safe Work Performing (IBWR), which is an annex to the Safety and Health Plan (Safety and Health Plan). It is important to remember that the site protection systems used should be certified and approved for use on railway lines. Rail transport is a particularly demanding area in terms of safety. The key to increasing its level is to continue existing and take new measures to promote the idea of safety. Automatic Warning Systems are still an innovative solution in Poland, which has been successfully proven in Europe for several years and is a safer option for the railway signalman. The system is responsible for the safe warning of railway traffic in the area of the repaired and adjacent track. Risks arising due to human fallibility or caused by human error are eliminated to a minimum. Keywords: Technological solutions; Trackway; Railway line